2016
DOI: 10.1007/s00198-016-3624-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and risk factors of postoperative pneumonia after hip fracture surgery: a prospective cohort study

Abstract: Intrinsic factors and major clinical interventions were all important risk factors of POP in patients after hip fracture surgery. Targeted preventive measures to mitigate the above risk factors may help in reducing the incidence of POP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
127
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(138 citation statements)
references
References 38 publications
8
127
1
2
Order By: Relevance
“…Similarly, Song et al [49] performed a prospective study on 111 TKA patients who had a postoperative pneumonia incidence of 14.4%. Lv et al [50] performed a retrospective study that included 1,429 patients who underwent hip fracture surgery, and had a 4.9% of incidence of postoperative pneumonia. Bohl et al [51] retrospectively reviewed 11,353 patients who underwent anterior cervical decompression and fusion, and found postoperative pneumonia had an incidence rate of 0.45%.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Song et al [49] performed a prospective study on 111 TKA patients who had a postoperative pneumonia incidence of 14.4%. Lv et al [50] performed a retrospective study that included 1,429 patients who underwent hip fracture surgery, and had a 4.9% of incidence of postoperative pneumonia. Bohl et al [51] retrospectively reviewed 11,353 patients who underwent anterior cervical decompression and fusion, and found postoperative pneumonia had an incidence rate of 0.45%.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, several variables, including male sex, ASA classification, dehydration and stroke, were identified as risk factors of aspiration pneumonia and other complications. In the current study, patients with aspiration pneumonia were more likely to be male, had higher ASA scores, and showed a greater frequency of dehydration and stroke; however, these differences were not statistically significant, except for the percentage of patients with an ASA score of ≄3.…”
Section: Discussionmentioning
confidence: 99%
“…Among older patients with hip fractures, pneumonia is the most common complication . It is associated with an increased risk of mortality in older hip fracture patients, and its risk factors have been identified …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pneumonia is also known to be a devastating complication after hip fracture surgery, which can also be life-threatening when correlative respiratory and circulatory failure was induced subsequently, and is especially risky to elderly patients who are more easily affected by the impactions of trauma and immobilization after fractures and surgeries. The reported incidence of pneumonia in elderly patients with a hip fracture was 1.2% preoperatively [22] and approximately 4% ~ 5% postoperatively according to recent literatures [14,15,21]. Although the overall incidence was not alarmingly great, it was found that patients who developed pneumonia would have a higher readmission rate, a higher rate of sepsis, and a higher mortality rate [15].…”
Section: Discussionmentioning
confidence: 99%